Perspektif Hak Asasi Manusia dalam Pemenuhan Atas Jaminan Hari Tua - Try Anggie Larasati; Dian Bakti Setiawan; Alsyam Alsyam (Lareh Law Review, 2023)
Old-Age Security (JHT) is an employment social security program that has the objective of providing cash benefits through a lump sum payment when participants enter retirement age, pass away, or experience permanent total disability. Where this mechanism is the embodiment of the mandate of Article 28H Paragraph (3) of the 1945 Constitution. However, the practice of implementing JHT has experienced several problems, for example changing implementing regulations in a short time, which raises two problems: First, regarding the dynamics of JHT arrangements in Indonesia, and the perspective of Human Rights in the implementation of JHT. This study uses a normative juridical method with library data collection techniques. This study concludes that the regulatory changes that have occurred in the regulations surrounding JHT are the government's efforts to adapt regulations to developments so that workers can enjoy JHT, but the government is not optimal in disseminating regulations to JHT beneficiaries. Meanwhile, from a human rights perspective, it can be concluded that the government is already present in realizing the fulfillment of the right to social security through JHT, which is through a legal umbrella in the form of Government Regulations and Ministerial Regulations. It's just that changing legal products in a short time is the main obstacle that has resulted in JHT not running optimally, so that workers have not been able to fully enjoy the fulfillment of their rights to JHT. Therefore, this study concludes that the government needs to create permanent regulations that do not require changes in a short time to fulfill JHT rights as a form of legal certainty.